COHESION AND COHERENCE ASPECTS IN THE STUDENTS WRITING PERFORMANCE AT SENIOR HIGH SCHOOLS - Gunas, Tobias (English Language Education Study Program, 2020)
Cohesion and coherence aspects are the essential components of writing, including descriptive and narrative texts. Those writing components are inevitably required to build a readable written text. This research mainly attempts to investigate the aspects of cohesion and coherence in the students writing tasks on descriptive and narrative text genres. 390 students were randomly selected as the subjects from thirteen senior high schools in Langke Rembong district. The students were assigned to write both descriptive and narrative text genres concerning the given prepared topics. The topics were familiar with the students. The data were analyzed in a descriptive quantitative model of analysis in light of percentages and counted scores. Accordingly, cohesion and coherence aspects were subsumed under some levels. The research revealed that cohesion and coherence aspects were poorly employed in the students writing. Only a smaller amount of the writings were partially cohesive and coherent texts, while most writings were fully incohesive and incoherent. Cohesion and coherence aspects found in the students descriptive and narrative texts were categorized into the lower level.